Human immunodeficiency virus and antiretroviral therapy-mediated immune cell metabolic dysregulation in children born to HIV-infected women: potential clinical implications - Mataramvura, Hope; Bunders, Madeleine J.; Duri, Kerina (Frontiers in Immunology, 2023)
Commencing lifelong antiretroviral therapy (ART) immediately following HIV diagnosis (Option B+) has dramatically improved the health of HIV-infected women and their children, with the majority being of HIV-exposed children born uninfected (HEU). This success has led to an increasing population of HIV-infected women receiving ART during pregnancy and children exposed to ART in utero. Nonetheless, a small proportion of children are still infected with HIV (HEI) each year. HEI children suffer from reduced immunocompetence and host-defence, due to CD4+ T lymphocyte depletion, but also dysregulation of other immune cells including CD8+ T lymphocytes, natural killer (NK) cells, macrophages including B lymphocytes. Furthermore, although HEU children are uninfected, altered immune responses are observed and associated with increased vulnerability to infections. The mechanisms underlying immune dysregulation in HEU children remain poorly described. Building on early studies, emerging data suggests that HIV/ART exposure early in life affects cell metabolic function of HEU children. Prenatal HIV/ART exposure has been associated with dysregulation of mitochondria, including impaired DNA polymerase activity. Furthermore, dysregulation of oxidative phosphorylation (OXPHOS) causes a decreased generation of adenosine triphosphate (ATP) and increased production of reactive oxygen species (ROS), resulting in oxidative stress. These altered metabolic processes can affect immune cell viability and immune responses. Recent studies have indicated that immune-metabolic dysregulation may contribute to HIV-associated pathogenesis and clinical observations associated with HIV and ART exposure in HEU/HEI children. Given the critical role metabolic processes in immune cell functioning, immune-metabolic dysregulation in HEU and HEI children may have implications in effective host-defence responses against pathogens, as well as efficacy of standard ART regimens and future novel HIV cure approaches in HEI children. At the same time, targeting metabolic pathways of immune cells may provide safer and novel approaches for HIV cure strategies. Here, we review the current literature investigating immune-metabolic dysregulation in paediatric HIV pathogenesis.